2003
DOI: 10.1063/1.1562163
|View full text |Cite
|
Sign up to set email alerts
|

Trapped ion effect on shielding, current flow, and charging of a small object in a plasma

Abstract: The problem of electrostatic shielding around a small spherical collector immersed in nonflowing plasma, and the related problem of electron and ion flow to the collector, date to the origins of plasma physics. Calculations have typically neglected collisions, on the grounds that the mean free path is long compared to the Debye length. However, it has long been suspected that negative-energy trapped ions, created by occasional collisions, could be important. This paper presents self-consistent analytic calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
164
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(178 citation statements)
references
References 23 publications
14
164
0
Order By: Relevance
“…These slow moving ions cannot escape the potential well and become trapped. The density of these trapped ions builds up over time, and they contribute to the enhancement of the peak amplitude with increased collisionality 32 . A similar discussion with regard to the calculation of drag forces on the grain can be found in Ref.…”
Section: B Influence Of Collisionalitymentioning
confidence: 99%
“…These slow moving ions cannot escape the potential well and become trapped. The density of these trapped ions builds up over time, and they contribute to the enhancement of the peak amplitude with increased collisionality 32 . A similar discussion with regard to the calculation of drag forces on the grain can be found in Ref.…”
Section: B Influence Of Collisionalitymentioning
confidence: 99%
“…Hence, it can be concluded that the effective shielding is done both by electrons and ions. Deviations of shielding lengths from ion Debye length have already been discussed in [15,44,56].…”
Section: Shieldingmentioning
confidence: 99%
“…There have been many refinements to the theory. Limitations and applicability of these theories have been dealt with previously in many articles [5][6][7][8][9][10][11][12][13][14][15] . More general Orbital Motion (OM) theory 7,8 involves solving simultaneously for the surface potential, the potential distribution around the probe, and the distribution of ion trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…If the ion has a larger angular momentum, it will probably orbit around the grain and be trapped in the potential well of the dust grain [35,36]. The trapped ions are likely to fall onto the grain surface after further collisions and therefore increase the ion current to the surface too.…”
Section: Ion-neutral Collisionsmentioning
confidence: 99%
“…The space time correlation function only depends on the distance between the particle positions r i − r j in a uniform system with translational invariance. Thus, without loss of generality the coordinate r ′ can be set to zero and the transformation between F het (q, t) and ρ r, t ρ r ′ , 0 can be written as 36) where V is the volume of the system. Here, a function widely used in DLS has to be introduced.…”
Section: Space Time Correlation Function Of the Particle Densitymentioning
confidence: 99%